China's Christian colleges : cross-cultural connections, 1900-1950 - Bays, Daniel H.; Widmer, Ellen (Stanford University Press, 2009)
China's Christian Colleges explores the cross-cultural dynamics that existed on the campuses of the Protestant Christian colleges in China during the first half of the twentieth century. Focusing on two-way cultural influences rather than on missionary efforts or Christianization, these campuses, most of which were American-supported and had a distinctly American flavor, were laboratories or incubators of mutual cultural interaction that has been very rare in modern Chinese history. In this Sino-foreign cultural territory, the collaborative educational endeavor between Westerners and Chinese created a highly unusual degree of cultural hybridity in some Americans and Chinese. The thirteen essays of the book provide concrete examples of why even today, more than a half-century after the colleges were taken over by the state, long-lasting cultural results of life in the colleges remain.
Keywords: Christian universities and colleges -- China -- History -- 20th century -- Congresses.; Education, Higher -- China -- History -- 20th century -- Congresses.; China -- Relations -- United States -- Congresses.; United States -- Relations -- China -- Congresses.; Electronic books.; Universités confessionnelles -- Chine -- Histoire -- 20e siècle -- Congrès.; Enseignement supérieur -- Chine -- Histoire -- 20e siècle -- Congrès.; Livres numériques.; e-books.; EDUCATION -- Higher.; Electronic books; Christian universities and colleges; Education, Higher; International relations; China; United States; Christentum; College; 1900-1999; Geschichte 1900-1950.; proceedings (reports); Conference papers and proceedings; History; Conference papers and proceedings.; Actes de congrès.